2018
DOI: 10.1159/000487795
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Helicobacter pylori-Naïve Early Gastric Cancers

Abstract: Aim: Helicobacter pylori-naïve gastric cancers(GCs) have not been well documented. We aimed to characterize early H. pylori-naïve GCs. Subjects and Methods: Of 666 patients with GC resected by endoscopic submucosal dissection, H. pylori-naïve patients were extracted according to the definition: no H. pylori eradication history, negative for serum H. pylori-antibody and current H. pylori-infection tests, and no gastric atrophy by pepsinogen (PG) test, endoscopy, and histology. Results: It was found that 16 GCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 21 publications
4
52
0
Order By: Relevance
“…The foveolar epithelial type is considered to develop from surface mucous cells, of which MUC5AC is a marker. This type of gastric cancer has been reported previously; the tumor was reported to spread laterally and with some degree of elevation, with villous or papillary surface, as we observed in the present study [26]. Unlike the undifferentiated type or the fundic gland type, the Dig Dis 2020;38:474-483 DOI: 10.1159/000506120 field of cancerization is superficial.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The foveolar epithelial type is considered to develop from surface mucous cells, of which MUC5AC is a marker. This type of gastric cancer has been reported previously; the tumor was reported to spread laterally and with some degree of elevation, with villous or papillary surface, as we observed in the present study [26]. Unlike the undifferentiated type or the fundic gland type, the Dig Dis 2020;38:474-483 DOI: 10.1159/000506120 field of cancerization is superficial.…”
Section: Discussionsupporting
confidence: 84%
“…Demarcation lines could be well recognized in lesions invading the submucosa, as tumor cells were not covered by normal mucosa, whereas in lesions invading the mucosa, it was difficult to detect demarcation lines because the tumor cells were not exposed. All lesions were of the undiffer- [24][25][26], 3 lesions (60%) in this study were observed to have invaded the submucosa. The IHC pattern did not show any regularity; some lesions were not only negative for MUC2 or CD10 but also for MUC6.…”
Section: Undifferentiated Typementioning
confidence: 45%
See 1 more Smart Citation
“…Signet ring cell carcinoma is well known as a typical histology of undifferentiated‐type HpUGC . In general, compared with PDA, SRCC progresses more slowly without massive invasion .…”
Section: Discussionsupporting
confidence: 61%
“…In Japan, the majority of patients with GC are Hp -positive, Hp -eradication, and Hp -uninfected GC accounts for <1% [3, 4]. However, as eradication therapy of Hp has been performed widely, the proportion of Hp -positive patients has gradually decreased, and Hp -uninfected GC is expected to increase relatively [5].…”
Section: Introductionmentioning
confidence: 99%